9 - Archie Mafeje and the Pursuit of Endogeny: Against Alterity and Extroversion - Adesina, Jimi O. (Africa Development, 2021)
Professor Archibald Monwabisi Mafeje passed away on 28 March 2007. The meaning of Archie Mafeje, for three generations of African scholars and social scientists, is profound and about diverse encounters. For some it was personal; for others it was through his works, and for most in the community the encounter via scholarly works became personal and intimate. The meaning of Mafeje for generations of African scholars is found in his uncompromising aversion to the ‘epistemology of alterity’ – the ‘othering’ of Africa and Africans – and the ad- vancement of scholarship grounded in the centring of African ontological expe- riences. It is in this aversion to alterity and pursuit of endogeneity that we locate Mafeje’s lasting legacy for new generations of African intellectuals. This paper, which is personal and intellectual, involves a close and critical engagement with these aspects of Mafeje’s scholarships.